Rheological, mechanical and durability properties of self-compacting mortars containing basalt powder and silica fume - Turk, Esra; Karatas, Mehmet; Dener, Murat (Elsevier Sci Ltd, 2022)
This study investigates the durability and mechanical performance of self-compacting mortars (SCMs) produced with basalt powder and silica fume. The novelty of the study lies in the use of both basalt powder and silica fume in the production of SCMs and investigating the sulfate resistance of the produced mortars. Different percentages of basalt powder (5%, 10%, 15%, 20%, 25%, 30%, 35% and 40%) and 10% of silica fume were used as a partial substitution of Portland cement. Mini slump-flow diameter and viscosity tests were carried out to evaluate the fresh properties of SCMs. Experiments were carried out to determine the effect of basalt powder and silica fume substitution on the mechanical properties, sorptivities, densities, water absorptions and sulfate resistances of the mortar specimens. Microstructural deteriorations after immersion in 10 wt% MgSO4 solution were analyzed by Fourier transform infrared spectroscopy. The experimental study indicated that the combined use of basalt powder and silica fume resulted in an improvement in strength. It was found that the long-term mechanical properties of SCMs containing up to 10% basalt powder were satisfactory. It was observed that the use of basalt powder had a positive effect against sulfate attack.
Keywords: Self-compacting mortar; Basalt; Silica fume; Sulfate resistance